Subject Olympiads as an effective tool of management personnel training in universities in modern conditions - I. O. Zakharova; S. N. Orlova (Вестник университета)
The present article studies the issue of using subject Olympiads in higher education institutions for effective training of managerial personnel on the example of the intra-university Olympiad in English language, held in November 2023 at the State University of Management. The quantitative and qualitative composition of participants by training areas and educational programs has been studied, sociological and didactic and methodological aspects of the Olympiad have been highlighted, individual tasks descriptions have been given, demonstrating their high practice-orientedness and relevance. The article concludes that participation in subject university Olympiads stimulates the interest of students of management specialties to the subject of study and increases their competence level. The competitive nature of the Olympiads contributes to a more successful subsequent adaptation of students to a highly competitive professional environment, creating conditions of healthy competition. Conducting subject competitions in universities solves the problems facing the system of higher education in terms of forming a creative educational environment that meets the challenges of the time, and training management specialists capable of effectively solving professional problems against the background of constantly changing economic and political situation in a tough external and internal environment.